'Soft Law in a Hard Shell': India, International Rulemaking and the International Solar Alliance. Issue 3 (15th November 2021) - Jha, Vyoma
Abstract: This article examines the creation of the International Solar Alliance (ISA), a new international organization led by India and backed primarily by developing countries. Official documents and wide-ranging interviews offer insights into the treaty-making process. Using a political economy approach to the study of international law, the article analyzes politico-legal issues associated with the creation of the ISA. The legal form of the ISA is best described as 'soft law in a hard shell': it uses the legal infrastructure of a treaty while relying on the social structure of participating actors for its future implementation. Empirical evidence suggests that three factors explain the treaty structure of the ISA: India's leadership role in the treaty-making process, the early involvement of non-state actors, and the preference of developing countries for legal form. Ultimately, the case illustrates India's shift towards a leadership role in climate change governance, and the steady emergence of non-state actors in driving climate action.